2019
DOI: 10.3897/natureconservation.34.30473
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of the trophic status in transitional ecosystems of the northern Adriatic Sea, key parameters and future expectations: The lagoon of Venice as a study case

Abstract: The determination of the trophic status of transitional ecosystems from the physico-chemical and biological point of view is one of the requirements of the European Water Framework Directive (WFD 2000/60/EC). In Italy, its determination is implemented by the Regional Agencies for Environmental Protection (ARPAs) that have activated multi-annual monitoring programs. However, as the availability of funds is increasingly scarce, the number of environmental parameters to detect environmental changes should be conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Increasing water transparency in the period 1998-2007 has been attributed to declining river discharge into the LoV (Bernardi Aubry et al 2013). More recently (2011-2014), the reduction in clam farming and the resurgence of macroalgae and seagrasses have also been cited as causes (Sfriso et al 2019). The overall increase in transparency during the period considered in this study is shown in Tables 2 and 3. Mean relative oxygen increased significantly and since 2012 has never fallen below 110%, although these levels are still way below those observed in the late 1980s and early 1990s.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Increasing water transparency in the period 1998-2007 has been attributed to declining river discharge into the LoV (Bernardi Aubry et al 2013). More recently (2011-2014), the reduction in clam farming and the resurgence of macroalgae and seagrasses have also been cited as causes (Sfriso et al 2019). The overall increase in transparency during the period considered in this study is shown in Tables 2 and 3. Mean relative oxygen increased significantly and since 2012 has never fallen below 110%, although these levels are still way below those observed in the late 1980s and early 1990s.…”
Section: Discussionmentioning
confidence: 77%
“…The overall increase in transparency during the period considered in this study is shown in Tables 2 and 3. Mean relative oxygen increased significantly and since 2012 has never fallen below 110%, although these levels are still way below those observed in the late 1980s and early 1990s. Indeed, that period saw average saturation levels of up to 250% in the central (Sfriso et al 2019) and northern lagoons (Bianchi et al 2000) due to the massive development of macro-and microalgae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980s, the gross production of nuisance macroalgae, mostly Ulvaceae, was about 18.5 million tons on a fresh weight (fw) basis [24]. In the following years, nutrient concentrations and macroalgal production strongly declined and, currently, they are one order of magnitude lower [25]. Water temperature ranges between −0.5 • C (with glaciation of canals and the inner areas between salt marshes) and over 40.0 • C (July 2019) in very choked areas.…”
Section: Methodsmentioning
confidence: 99%
“…The long-term analysis of various ecosystem components has also proved to be useful to identify key variables that may allow environmental dynamics to be followed in view of possible future limitations of sampling or analytical efforts. This is the case of tintinnids for marine microzooplankton (Monti-Birkenmeier et al 2019), taxonomic surrogates for benthic assemblages in transitional ecosystems (Pitacco et al 2019) and nutrients, such as nitrites and reactive phosphorus for the trophic status of the Venice Lagoon (Sfriso et al 2019). The value of LTER investigations, generally conducted at a single site, is further enhanced by expanding the spatial scale of the observations in a comparative effort, which is especially useful for the prediction of future changes in marine systems in response to climate variability and ocean warming (Kröncke et al 2019).…”
mentioning
confidence: 99%